A COMPERATIVE INTERPRETATION OF ENGLISH AND UZBEK FRACTURED AND MODIFIED FAIRY TALES (International Conference on Educational Discoveries and Humanities, 2025)
Fairy tales remain one of the most malleable and enduring literary forms: as societies change, so do their narratives. In the contemporary era, classical folk and literary tales are increasingly being modernized and re-written. These adaptations reflect new cultural norms, address current social issues, and reinterpret traditional archetypes. At the same time, the way fairy tales are understood (“interpretation”) differs in English-speaking contexts versus Uzbek contexts, shaped by their respective literary traditions and cultural values. Thematic Renewal: Modern retellings often engage with themes that resonate today — such as gender equality, identity, social justice, and environmental concerns.